Physical (A)Causality Determinism, Randomness and Uncaused Events - Svozil, Karl (Fundamental Theories of Physics, 2018)
Physical indeterminism; Randomness in physics; Physical random number generators; Physical chaos; Self-reflexive knowledge; Acausality in physics; Irreducible randomness